Guy COOK. The Discourse of Advertising. London: Routledge. 2001. 256 pp. Second Edition. ISBN 0-415-23455-7 - Pinto, Alexandra (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
.